Talking with Friends About Sex, and Why We Don't. - Gourlay, Kenneth (Sexuality & Culture, 2024)
Healthy and honest discussions about sexuality provide individuals with more fulfilling and successful romantic relationships and better sexual health outcomes. Honest understanding of sex and sexual issues can also encourage more successful negotiation of sexual consent and better public policy. Additionally, peers have consistently been among those with whom individuals are most comfortable discussing sexuality. However, little research has sought to analyze peer sexual communication. Building on a study of sexual communication in romantic partnerships, this study assesses individuals' perceived social and personal barriers to openly discussing their sex and sexuality with close friends. The study uses a survey experiment to test for differences in perceived barriers to participating in a group discussion among friends when the topic relates to sexuality versus a general topic. Barriers to communication are not found to be stronger in sexual discussions overall, but they are stronger for those with marginalized sexual identities or greater general mental distress. Discussion identifies avenues for future research and suggests alternative theoretical frames for better understanding differences across sexual orientations and identities.